2019
DOI: 10.3390/polym11121916
|View full text |Cite
|
Sign up to set email alerts
|

Development of Coffee Biochar Filler for the Production of Electrical Conductive Reinforced Plastic

Abstract: In this work we focused our attention on an innovative use of food residual biomasses. In particular, we produced biochar from coffee waste and used it as filler in epoxy resin composites with the aim to increase their electrical properties. Electrical conductivity was studied for the biochar and biochar-based composite in function of pressure applied. The results obtained were compared with carbon black and carbon black composites. We demonstrated that, even if the coffee biochar had less conductivity compare… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 59 publications
5
62
0
Order By: Relevance
“…It was collected from Bar Katia (Turin, Italy) supplied by Vergnano Spa (Torino, Italy) and corresponds to an Arabica mixture. The exhausted coffee was collected and dried at 105 • C for 72 h. Coffee samples (100 g) were pyrolyzed using a vertical furnace and a quartz reactor (heating rate: 15 • C/min) and kept at 800 • C for 30 min in argon atmosphere [19][20][21].…”
Section: Methodsmentioning
confidence: 99%
“…It was collected from Bar Katia (Turin, Italy) supplied by Vergnano Spa (Torino, Italy) and corresponds to an Arabica mixture. The exhausted coffee was collected and dried at 105 • C for 72 h. Coffee samples (100 g) were pyrolyzed using a vertical furnace and a quartz reactor (heating rate: 15 • C/min) and kept at 800 • C for 30 min in argon atmosphere [19][20][21].…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, in the case of melt mixed composites, the BC particles' average size seems to be lower than that observed for solvent cast systems. This phenomenon can likely be ascribed to the intense shear stresses that BC underwent during melt mixing, as during the processing, a partial disruption of particles may occur [39]. This finding can explain the different rheological behavior showed by melt mixed composites with respect to the solvent cast ones, as the size decrease of the BC particles could cause an increase of the polymer/filler interfacial area with a consequent amplification of the interactions between BC and PLA macromolecular chains.…”
Section: Morphologymentioning
confidence: 99%
“…The beneficial effects of biochar addition to epoxy composites have reported by many studies . Giorcelli et al . reported the use of high thermal treated biochar for the production of conductive epoxy composite while other studies reported the improvement of mechanical properties of biochar containing reinforced plastics .…”
Section: Introductionmentioning
confidence: 99%